2019
DOI: 10.1210/js.2019-sat-139
|View full text |Cite
|
Sign up to set email alerts
|

SAT-139 Clinical Impact of Oral Semaglutide Compared with Sitagliptin in T2D on Metformin ± Sulfonylurea: The Pioneer 3 Trial

Abstract: Long-term effects, safety and tolerability of oral semaglutide (SEMA; a GLP-1 receptor agonist [GLP-1RA]) vs sitagliptin (SITA) as add-on to metformin ± sulfonylurea was investigated in patients (pts) with T2D in a 78-week, double-blind, double-dummy trial. Pts were randomized to once daily oral SEMA 3 mg (N=466), 7 mg (N=466) or 14 mg (N=465), or SITA 100 mg (N=467). Primary endpoint was change in HbA 1c , confirmatory secondary endpoint was change in body weight, both from baseline to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…There is significant evidence that people with type 2 diabetes in the US, UK and worldwide do not intensify treatment, despite not achieving glycemic control targets, with concerns around potential side effects of therapies (such as weight gain and hypoglycemia) and fear of injection often cited as reasons for therapeutic inertia [1822]. The oral formulation of semaglutide allows people with type 2 diabetes to receive the benefits of treatment with a GLP-1 receptor agonist, such as improved glycemic control without weight gain and a low risk of hypoglycemia, without the requirement for daily or weekly injections [911]. The present analysis demonstrated that oral semaglutide is efficacious and cost-effective in varying patient populations versus comparators for patients with type 2 diabetes receiving differing background therapies, indicating it is a viable treatment option for a variety of patients, irrespective of prior treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant evidence that people with type 2 diabetes in the US, UK and worldwide do not intensify treatment, despite not achieving glycemic control targets, with concerns around potential side effects of therapies (such as weight gain and hypoglycemia) and fear of injection often cited as reasons for therapeutic inertia [1822]. The oral formulation of semaglutide allows people with type 2 diabetes to receive the benefits of treatment with a GLP-1 receptor agonist, such as improved glycemic control without weight gain and a low risk of hypoglycemia, without the requirement for daily or weekly injections [911]. The present analysis demonstrated that oral semaglutide is efficacious and cost-effective in varying patient populations versus comparators for patients with type 2 diabetes receiving differing background therapies, indicating it is a viable treatment option for a variety of patients, irrespective of prior treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There were fewer serious adverse events with oral semaglutide than empagliflozin. PIONEER 3 was a 78-week, multinational, randomized, double-blind trial that compared the long-term efficacy, safety, and tolerability of oral semaglutide 3, 7, or 14 mg with the dipeptidyl peptidase-4 inhibitor, sitagliptin, in 1864 patients (including 207 patients from Japan) with type 2 diabetes uncontrolled on metformin with or without a sulfonylurea [47]. Oral semaglutide 7 and 14 mg resulted in superior HbA 1c reductions vs. sitagliptin at week 26 (estimated treatment differences of − 0.3% and − 0.5%, respectively), with this effect maintained to week 78 for the 14 mg dose (Fig.…”
Section: Pioneermentioning
confidence: 99%
“…In the background medication subgroups, 3 -17% of patients experienced serious adverse events, and up to 17% of patients quit their prescribed medicine permanently [57]. In case of oral semaglutide 3, 7 or 14 mg the number of subjects who experienced gastrointestinal adverse events (mostly during dose escalation in the first 8 -16 weeks) and the number of subjects who discontinued the trial due to these symptoms, appeared to rise with the dose [3,6,63,79]. Accordingly, to these observations, a dosage-escalation strategy is suggested, beginning with a low dose (3 mg) to prevent gastrointestinal adverse effects [67].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Accordingly, to these observations, a dosage-escalation strategy is suggested, beginning with a low dose (3 mg) to prevent gastrointestinal adverse effects [67]. Despite patients receiving background basal/bolus insulin treatment in PIONEER 8 trial [79], oral semaglutide patients had a low frequency of symptomatic, blood glucose-confirmed hypoglycaemia, and its incidence did not surpass 8% in any treatment group [6,10,42,[55][56][57][58][59][60][61][62][63]69]. As for special patient populations, individuals with an e-GFR lower than 60 mL/min/1.73 m 2 had a greater proportion of severe gastrointestinal adverse effects than those with e-GFR > 60 mL/min/1.73 m 2 , although significant hypoglycaemic episodes were rare [42].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%